Photosynthetic Microbes as Bioindicator for Nanoparticles in Aquatic Environment: A Review - Foo, Carolyn Zi Yan; Tan, Yeong Hwang; Wong, Ling Shing; Sinouvassane, Djearamane (INTI International University, 2022)
The intensive usage of nanoparticles such as Ag, ZnO, and TiO2 in industries inevitably leads to environmental pollution, especially in the water ecosystem. The bio-uptake and accumulation of nanoparticles in aquatic environments can lead to dire consequences to the flora and fauna, thereby affecting the whole food chain. Photosynthetic microorganisms such as microalgae and cyanobacteria are found abundantly in the natural environment which may be affected by the presence of nanoparticles in the environment, due to their high sensitivity to the presence of pollutants. The present review highlighted the photosynthetic responses after exposure of microalgae and cyanobacteria to these nanoparticles. The different parameters studied on the photosynthetic responses are algal growth, chlorophyll fluorescence emission, algal biomass, primary metabolic content (carbohydrates, lipids, and protein), and the microscopic examination of algae after exposure were summarized and discussed. The effective concentration of microalgae and cyanobacteria was also further investigated in determining the algae with the highest sensitivity as the best potential bioindicator for nanoparticle toxicity in an aquatic environment.